2016
DOI: 10.3892/or.2016.5108
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein inhibits TNF-α-induced NF-κB activation and expression of NF-κB-regulated target gene products

Abstract: The nuclear factor-κB (NF-κB) transcription factors control many physiological processes including inflammation, immunity, apoptosis and angiogenesis. In our search for NF-κB inhibitors from natural resources, we identified baicalein from Scutellaria baicalensis as an inhibitor of NF-κB activation. As examined by the NF-κB luciferase reporter assay, we found that baicalein suppressed TNF-α-induced NF-κB activation in a dose-dependent manner. It also inhibited TNF-α-induced nuclear translocation of p65 through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 20 publications
(18 reference statements)
5
28
0
Order By: Relevance
“…Some inflammatory cytokines could activate I-κBα, and then p65 protein separates from I-κBα and translocates from cytoplasm to the nucleus to bind related inflammation genes to induce inflammation [18]. Many studies provide evidence for the role of NF-κB in mediating enhancement of apoptosis [14,15]. Apoptosis, or programmed cell death, has been suggested to have a close relationship with OA progression [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some inflammatory cytokines could activate I-κBα, and then p65 protein separates from I-κBα and translocates from cytoplasm to the nucleus to bind related inflammation genes to induce inflammation [18]. Many studies provide evidence for the role of NF-κB in mediating enhancement of apoptosis [14,15]. Apoptosis, or programmed cell death, has been suggested to have a close relationship with OA progression [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor κB (NF-κB) has been considered as a central mediator in diverse cellular responses, particularly in the inflammatory process and immune response [9]. Many studies reported that IL-1β and TNF-α induced the nuclear translocation of NF-κB [10][11][12][13][14]. en, NF-κB activated the downstream Bcl-2 family proteins to regulate apoptosis [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism that would potentially explain both the apoptotic and protective effects is the inhibitory action of NF-κB and its-regulated gene expression by Baicalein. Baicalein induced apoptosis in cancer cells by suppression of anti-apoptotic Bcl-2 family proteins via the inhibition of NF-κB (Li et al, 2016). Meanwhile, Baicalein exhibited protective effects mediated by the suppression of iNOS via NF-κB inhibition (Suk et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…[53][54] Not only esculin but also gingerol, baicalein, and wogonin, another active compound interacted with baicelein, have interaction with MMP9 and TNF-α and moreover, some studies have been approved these compounds' effect toward MMP9 and TNF-α. [55][56][57] In tuberculosis treatment, it may be suggested that esculin, gingerol, wogonin, and baicelin reduce the level of TNF-α and MMP9. Furthermore, zingerone found in Zingiber officinallis Rosc also have interaction with TNF-α through catalase.…”
Section: Plants Used For Treating Tuberculosis In Indonesia Provincesmentioning
confidence: 99%